Prebiotics enhance persistence of fermented-food associated bacteria in in vitro cultivated fecal microbial communities - Christensen, Chloe M.; Kok, Car Reen; Auchtung, Jennifer M.; Hutkins, Robert (Frontiers in Microbiology, 2022)
It is well established that the gastrointestinal (GI) microbiota plays a major role in human health. Dietary interventions, and consumption of fermented foods that contain live microbes, in particular, are among the approaches being investigated to modulate the GI microbiota and improve health. However, the persistence of fermented food-associated bacteria (FAB) within the GI tract is typically limited by host factors that limit colonization and competition with autochthonous microbes. In this research, we examined if the addition of prebiotics, dietary substrates that are selectively metabolized by microbes to improve health, would enhance the persistence of FAB. We evaluated the persistence of bacteria from three live microbe-containing fermented foods – kefir, sausage, and sauerkraut – in fecal microbial communities from four healthy adults. Fecal communities were propagated in vitro and were inoculated with fermented food-associated microbes from kefir, sausage, or sauerkraut at ~107 CFU/ml. Communities were diluted 1:100 every 24 hours into fresh gut simulation medium to simulate microbial community turnover in the GI tract. We measured the persistence of Lactobacillaceae from fermented foods by quantitative PCR (qPCR) and the persistence of other FAB through 16S rRNA gene sequencing. FAB were unable to persist in vitro, reaching undetectable levels within 96 hours. Addition of prebiotics, including xylooligosaccharides and a mixture of fructooligosaccharides and galactooligosaccharides enhanced the persistence of some species of FAB, but the level of persistence varied by fecal donor, fermented food, and prebiotic tested. Addition of prebiotics also increased the relative abundance of Bifidobacterium species, which most likely originated from the fecal microbiota. Collectively, our results support previous in vivo studies demonstrating the transient nature of FAB in the GI tract and indicate that consumption of prebiotics may enhance their persistence.